A Way of Life: Indigenous Perspectives on Anti-Oppressive Living - Thomas, Robina; Green, Jacquie (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2019)
The focus of this article is on the key elements of anti-oppressive practices as examined by two Indigenous women who practice and teach anti-oppressive ways. Anti-oppressive living is characterized as a Way of Life that values the sacred and traditional teachings of various Indigenous cultures. The Medicine Wheel is discussed and highlighted as an effective teaching tool to examine anti-oppressive ways of living, practicing, and perspectives.